Morphological and lexical variations of Isnag, Isneg Yapayao, and Itneg Tingguian as spoken in Ilocos Norte (2015)
This study looked into the morphological and lexical variations of Isnag, Isneg Yapayao, and Itneg Tingguian as spoken in Ilocos Norte in terms of nouns, pronouns and deixis, verbs, adjectives, and negation and interrogatives. These three language varieties that coexist with Ilocano, the lingua franca of Ilocos regions, are spoken in ten municipalities in Ilocos Norte, particularly in three major areas where indigenous communities are located, namely, Carasi, Dumalneg, and Nueva Era. Such an analysis was done to initially describe the morphological and lexical variations of languages spoken by the three groups of indigenous people (IP) of Ilocos Norte, and to help provide the Province, particularly the National Commission on Indigenous People-Ilocos Norte Provincial Office (NCIP-INPO), a reference material for future studies on the linguistic profile of the IP. Data were gathered through a 158-item lexical test among 90 participants, with 30 each from the three IP groups. Responses were analyzed following Dita’s (2011) structural analysis of Ibanag nominal markers and Ruffolo’s (2004) morphophonemic analysis of Ibaloy. Based on the morphological and lexical analysis made, reduplication pattern (CV and CVC) is commonly used to denote plurality of nouns across the three language varieties. While ISA uses daya as a plural marker, ITE uses adu a and dia. While ISA and ISE are lexically different from each other in terms of the use of gender-specific nouns, ITE is lexically closer to Ilocano. All personal pronouns across the three languages differ. While ITE possessives follow the same morphological process as ISE, the latter was found to be somewhat similar with Ilocano possessives. All of the deictic demonstratives were encoded entirely differently across the three languages. ISA, ISE, and ITE inflect their lexical verbs by reduplication, phonemic substitution, and affixation. The three language varieties have monomorphemic as well as derived adjectives just like their Ilocano counterparts. Most quantification terms and interrogatives were found to be varied across the three languages. Among the language varieties, ISA was found to be morphologically and lexically different from ISE and ITE.
Keywords: Variation in language; Ilokano language